The crucible of early career psychiatry. (June 2019) - Ng, Lillian; Steane, Richard; Scollay, Natalie; Harris, Stephen; Milosevic, Jasminka; Young, Kirsten; Tan, David; Chow, Samantha
Objective: To capture the voices of psychiatrists as they reflect on challenges at the early stages of the career trajectory. Method: Early career psychiatrists contributed reflections that identified various challenges in the transition from trainee to consultant psychiatrist. Results: Common difficulties included negotiating role transition and conflict. Specific events had deep impact such as involvement with a patient who had committed suicide. Conclusions: Challenges in the early career stage as a consultant psychiatrist may have lasting or career defining impact. Written reflection is a valuable tool that can impart collective learning, provide validation and engender support among peers.